Guidelines Protocol for Enhance Nurses’ Performance for Care of Children with Respiratory Disorders on Oxygen Therapy and Pulse Oximetry - Helaly, Nadia Medany; Sobky, Fatma Ahmed El (International Journal For Research In Health Sciences And Nursing, 2020)
Background: Pulse oximetry is a noninvasive method that enables rapid measurement of the oxygen saturation of hemoglobin in arterial blood, it important for the quality of healthcare and the infant's safety. The aim of the study: The aim of the current study was to develop and evaluateguidelines protocol to enhance nurses’ performance for the care of children with respiratory disorders on oxygen therapyand pulse oximetry. Design: A quasi-experimental design was used. Setting: The study carried out in theNICU and PICU on the pediatricdepartment at Maternity & Children Hospital in Alexandria. Sample: A convenient sample of 100 nurses worked at the NICU, and PICU in pediatric department were enrolled in this study. Tools:Three tools were used to collect the study data, Tool I;a structured interviewto assess the basic characteristics of the nurses as well their knowledge aboutrespiratory disorders, pulse oximetry, and oxygen therapy. Tool II;an observational checklist to evaluate nurses’ performance regarding pulse oximetry, and oxygen therapy. Results: The study results revealed that after the implementation ofguidelines protocol the nurseshad a satisfactory level of knowledge and performance regarding pulse oximetry and oxygen therapy. Conclusion: The guidelines protocol of pulse oximetry and oxygen therapy has a good effect on nurses’ knowledge and performance among children with respiratory disorder. Recommendation:Continuous updates of nurses’ knowledge and performance regarding pulse oximetry and oxygen therapy.